Within and between year phenology of calling Spotted Crakes Porzana porzana in Denmark - Fox, Anthony D.; Kjeldsen, Jørgen P.; Desholm, Mark; Rasmussen, Palle A.F.; Balsby, Thorsten J.S.; Heldbjerg, Henning (Wildfowl, 2014)
Analysis of data relating to calling Spotted Crakes Porzana porzana, input to the Danish Citizen Science portal DOFbasen, suggested that on controlling for observer effort, national numbers reported annually have remained reasonably stable during 1981–2013, but with large influxes in a very few years, mostly due to large arrivals late in the season in June/July. Standard annual mapping of calling birds at Vejlerne, numerically the most important breeding area for the species in Denmark, correlated well with annual national indices over the same period of years. Calling birds mapped at Vejlerne and those reported to DOFbasen both showed a consistent bimodal pattern, with peaks in April/May and June/July, although the relative size of the second peak in particular varied between years. We speculate on the causes of these two peaks in calling activity which both potentially relate to birds defending territories and intending to breed. The often large late influx, and the occupancy of different territories during the second peak compared to the first, suggested the second wave of birds were different individuals to those recorded earlier in the season. Radio telemetry showed early breeding birds to be still present but silent during the second peak in calling activity, suggesting a new wave of late arriving birds in July (possibly from areas to the south or elsewhere where they may previously have attempted to breed) which potentially also attempt to breed in Denmark. We recommend continuing radio telemetry studies to confirm whether the same individuals call in both periods, supplemented by high quality sound recordings to differentiate individuals on the basis of their calls and assess the existence of any recognisable dialects across Europe. Stable isotope analysis of feathers grown outside the breeding areas would also help to provide a better understanding of the breeding status, origins and relative abundance of calling birds in these two waves.